Impact of Chromium Picolinate on Leydig Cell Steroidogenesis and Antioxidant Balance Using an In Vitro Insulin Resistance Model - Rúben Moreira; Ana D. Martins; Rita Ferreira; Marco G. Alves; Maria de Lourdes Pereira; Pedro F. Oliveira (Antioxidants, 2023)
Leydig cells (LCs) play a pivotal role in male fertility, producing testosterone. Chromium (III) picolinate (CrPic3), a contentious supplement with antidiabetic and antioxidant properties, raises concerns regarding male fertility. Using a rodent LC line, we investigated the cytotoxicity of increasing CrPic3 doses. An insulin resistance (IR) model was established using palmitate (PA), and LCs were further exposed to CrPic3 to assess its antioxidant/antidiabetic activities. An exometabolome analysis was performed using 1H-NMR. Mitochondrial function and oxidative stress were evaluated via immunoblot. Steroidogenesis was assessed by quantifying androstenedione through ELISA. Our results uncover the toxic effects of CrPic3 on LCs even at low doses under IR conditions. Furthermore, even under these IR conditions, CrPic3 fails to enhance glucose consumption but restores the expression of mitochondrial complexes CII and CIII, alleviating oxidative stress in LCs. While baseline androgen production remained unaffected, CrPic3 promoted androstenedione production in LCs in the presence of PA, suggesting that it promotes cholesterol conversion into androgenic intermediates in this context. This study highlights the need for caution with CrPic3 even at lower doses. It provides valuable insights into the intricate factors influencing LCs metabolism and antioxidant defenses, shedding light on potential benefits and risks of CrPic3, particularly in IR conditions.